Health-related quality of life in postcardiac interventional catheterization patients with congenital heart disease: a mixed-methods study protocol from Pakistan. Issue 12 (30th December 2021) - Ali, Fatima; Ladak, Laila Akbar; Usmani, Asra Abeer; Raza, Hussain Ahmed; Siddiqui, Marium Tariq; Hasan, Babar
Abstract : Introduction: Improvement in health-related quality of life (HRQoL) has been reported in patients with congenital heart disease treated with interventional cardiac catheterization; however, there is a significant dearth of literature from low/middle-income countries (LMICs) about this aspect. Multiple factors like sociodemographic and cultural differences, variable procedural outcomes due to lack of technical expertise and limited resources and inconsistent postprocedure follow-up may affect HRQoL in LMICs. This protocol paper aims to describe the study methodology to determine the HRQoL and its predictors in patients who have undergone interventional cardiac catheterization. Conclusions from this protocol study will help prepare a holistic approach to delivering care to patients in low-resource settings. Methods and analysis: A mixed-methods study design will be used. The quantitative arm will compare the HRQoL of these postcardiac interventional catheterization patients with their age-matched healthy siblings to identify the HRQoL predictors, whereas the qualitative arm will further explore the experiences of these patients and parents. A minimum number of 108 patients of age 2 years and above, at least 6 months postinterventional catheterization follow-up and ability to understand Urdu/English will be enrolled. PedsQL 4.0 Generic Core Scales, PedsQL Cognitive Functioning Scale and PedsQL 3.0 Cardiac Module will be used. The Student's t-test will analyse the difference in the means of HRQoL between patients and siblings. Multiple regression will identify HRQoL predictors. A subsample of enrolled patients and parents will be interviewed and analysed using directed content analysis (a qualitative component of the study). Ethics and dissemination: Ethics approval has been obtained from Ethics Review Committee of The Aga Khan University, Pakistan (ERC #2020-3456-11808). Study findings will be published in peer-reviewed journals and presented at conferences.